ARTE NA ESCOLA: A DIMENSÃO DO PROCESSO CRIATIVO NA RELAÇÃO PEDAGÓGICA - Tavares, Andrea Cristina de Paula (2012)
The study in this research focuses on furthering the discussions and reflections on the creative process and its importance in relation to pedagogical practices of teachers from the Arts. When discussing the process of creating and testing the student in the school context, what possibilities, limits and barriers manifest themselves? This is a qualitative research, carried out based on theoretical literature, taking as reference: Paulo Freire (2007) and his discussion of the importance of relationship-building for the teaching of learner autonomy, Ana Mae Barbosa (2008) and his studies of art-education in Brazil and teacher of Art, the Art National Curriculum (1998) with emphasis on the joint recommendation on the three axes methodology: creation / production art, aesthetic enjoyment, and reflection ; Porcher (1982) and his discussion of the importance of Arts Education and Albano (1998) with his account of the experience between the artist Tarsila do Amaral and his apprentice Tuneu. The field research was carried out with interviews with three teachers of Art and three students (one student from each teacher), two state schools in the Public School of Sao Bernardo do Campo and a state school in the Public School Diadema. For the treatment of the data collected in the interviews was used Content Analysis Methodology proposed by Franco (2008). Data analysis showed that the processing of ideas, experimentation and the whole creative process of the student is almost always overlooked in its importance as a pedagogical practice developed in the context of school art classes. The data presented in the survey, regarding teacher training, indicate a high degree of formation, but when compared to teaching practice, perceive gaps about the important role of the pedagogical relationship in the creative process of the student. Despite this present itself as a reality in the research, could not fail to mention that even with a small representation, we observed a positive practical methodology which crystallizes the creative process of the student as a way of building autonomy, where the student is presented with a list educational experience that promotes the build and all forms of expression, to make active, to express their world view.